Skop, Sejarah dan Aliran Pemikiran Islam - Hj Ab Majid, Mohd Kamil (Jurnal Usuluddin, 2017)
The article attempts to explicate the definition and scope and to give a brief history of Islamic thought and its two streams, i.e. the modernist and the traditionalist. The two streams tries to solve the crisis in the thought by their own ways which when analysed have their own weaknesses and strength. The infra-structure which can bring the two streams to a common ground needs to be identified to encourage intellectual and political co-operation which can lead to the excellence of tajdid hadari.